From Policy Ambition to System Capacity: Understanding Misalignment in Indonesia’s Decentralized Health Governance - Muslim Afandi; Syed Agung Afandi; Rizki Erdayani (Journal Sovereignty Law And Diplomatic Politics, 2025)
This article analyzes the planning, implementation, and monitoring of health policy in Indonesia within the context of decentralization and ongoing health system reforms. Despite progress toward near-universal coverage through the National Health Insurance, persistent structural challenges continue to hinder equitable outcomes. Key issues include uneven institutional capacity across regions, financing distortions, and varied adoption of digital systems such as SATUSEHAT. Using a systematic and integrative review of academic literature, government regulations, and national evaluation reports from 2000 to 2025, the study employs a hybrid deductive–inductive thematic analysis guided by the Policy Triangle, Street-Level Bureaucracy, the Advocacy Coalition Framework, and the WHO Health System Building Blocks. Findings indicate misalignment between national policy design and subnational implementation capability, shaped by fiscal disparities, leadership quality, bureaucratic stability, and managerial competence. These factors contribute to variations in maternal health outcomes, tuberculosis control, and noncommunicable disease management. Weak monitoring and evaluation—reflected in inconsistent data quality and a compliance-driven reporting culture—limits adaptive governance. The article proposes an adaptive governance framework emphasizing typology-based strategies, equity-oriented resource allocation, strengthened analytical capacity, and integrated health information systems. It concludes that future reforms require governance coherence and institutional capacity strengthening across all levels.